Pengaruh Sistem Informasi SDM, Kompetensi, dan Disiplin Kerja terhadap Kinerja Karyawan Pada Purana Boutique Resort Ubud - Mantari, Kadek Dwi; Dwi Mantari, Ni Kadek; Risma Mega Arsha, I Made (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
Employee performance, representing the quality and quantity of tasks accomplished by individuals as per their assigned responsibilities, stands as a critical outcome in organizational settings. This study aims to investigate the impact of human resources information systems, competence, and work discipline on employee performance. Conducted at Purana Boutique Resort Ubud, the research encompassed a population of 37 employees, employing a saturated sampling technique where all members of the population were included as research subjects. Data collection methodologies comprised observation, interviews, documentation review, literature study, and the administration of a questionnaire utilizing a five-point Likert scale ranging from strongly disagree (1) to strongly agree (5). Subsequently, the analysis incorporated multiple linear regression analysis, coefficient of determination analysis, T-test, and F-test to explore the relationships among the variables. The results of hypothesis testing indicate that human resources information systems, competence, and work discipline, both partially and simultaneously, have a significant positive effect on employee performance. The determination test results show that the ability of human resources information systems, competence, and work discipline in influencing employee performance is 85.9%. Recommendations for Purana Boutique Resort Ubud include enhancing employee performance by paying attention to these aspects. Future research can expand the scope to other types of companies and increase the sample size for more representative results regarding employee performance.